A New Indicator for Describing Bull and Bear Markets - German Forero-Laverde (European Historical Economics Society (EHES), 2018)
Abstract We present new short, medium, and long-run indicators to date and characterise expansions and contractions in financial and economic time series. These Bull-Bear Indicators (BBIs) measure the risk-adjusted excess return with respect to average, to different time horizons, expressed in standard deviations. We illustrate the benefits of this measure by describing the boom-bust cycle in the UK stock market between 1922 and 2015. We compare our results with those obtained from frequently used methodologies in the literature and find that our measures contain substantially more information than the usual binary sequences that describe expansions and contractions and allow for a more granular and nuanced description of time series.
Keywords: C1; C43; E32; G01; G1; N14; 330; Boom-bust cycle; Bull and bear markets; Stock market; Time series analysis; Severity measures; Dating rules